Books: Morgan, G. A., Liao, H. F., & Józsa, K. (2020). Assessing Mastery Motivation in Children Using the Dimensions of Mastery Questionnaire (DMQ). Gödöllő: Szent István University. ISBN: 978-963-269-922-6. - Suherman, Suherman (Acta Paedagogica Vilnensia, 2022)
-
Keywords: -